Effect of Milling Time on Surface Morphology of AISI O1 - Guo, Kelvii Wei (Journal of Coating Science and Technology, 2018)
AISI O1 was processed by surface milling and the influence of milling time on the surface morphology was studied by 3D profilometer and scanning electron microscopy (SEM). Results show that when AISI O1 specimens are processed with various milling time, the morphology of AISI O1 changes correspondingly. Moreover, it demonstrates that the initial increase in milling time accompanies with the increase in surface roughness until the milling time reaches 60 min at which the surface roughness is the minimum